The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/polym14204372
|View full text |Cite
|
Sign up to set email alerts
|

Waste Eggshells as a Natural Filler for the Poly(Vinyl Chloride) Composites

Abstract: The paper presents the characteristics of unplasticized PVC composites modified with biofiller obtained from the waste eggshells of hen eggs. The composites obtained by extrusion contained from 10 phr to 40 phr of biofiller. The filler was characterized using the SEM, TG, and sieve analysis methods. The influence of the filler on the processing properties was determined using plastographometric and MFR tests. Fundamental analysis of mechanical properties was also performed, i.e., Charpy impact strength and det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…The residue after decomposition at 1100 • C was 51.4% for eggshells and 57.2% for CaCO 3 , respectively. Therefore, the ground eggshells contained of approximately 94% mineral compounds, i.e., CaCO 3 , whereas the organic part was approximately 6% mineral compounds, which is consistent with the literature [49,56].…”
Section: Characterization Of Pure Ground Eggshellssupporting
confidence: 91%
See 1 more Smart Citation
“…The residue after decomposition at 1100 • C was 51.4% for eggshells and 57.2% for CaCO 3 , respectively. Therefore, the ground eggshells contained of approximately 94% mineral compounds, i.e., CaCO 3 , whereas the organic part was approximately 6% mineral compounds, which is consistent with the literature [49,56].…”
Section: Characterization Of Pure Ground Eggshellssupporting
confidence: 91%
“…In the case of CaCO 3 , the mass loss in the temperature range of 650-900 • C was attributed to the emission of gaseous carbon dioxide (CO 2 ) [49,52,53]. The presence of a similar mass loss on the TG curve of eggshells in the temperature range of 650-900 • C confirmed that the eggshells contained CaCO 3 .The removal of CO 2 from CaCO 3 led to the calcium oxide (CaO) as a mineral residue after thermal decomposition [54][55][56]. The residue after decomposition at 1100 • C was 51.4% for eggshells and 57.2% for CaCO 3 , respectively.…”
Section: Characterization Of Pure Ground Eggshellsmentioning
confidence: 95%
“…261 °C is associated with an intensive decomposition of plasticiser, while the T DTG3 maximum of approx. 293 °C is associated with the dechlorination of PVC macromolecules [ 45 , 52 ]. The next stage above 400 °C is attributed to the crosslinking of chains containing C=C bonds, as the process of thermal degradation of polyenes involves cyclization and the splitting of chains [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…The relatively small amplitude and low strain frequency allow for a measurement in a linear viscoelastic range with a low value of the loss modulus [ 44 ]. The glass transition temperature ( T g ) was determined based on changes in the value of the storage modulus (E′) as a function of temperature at the beginning of a rapid decrease in value E′ ( T g onset) [ 45 ]. From the DMA thermograms obtained, the maximum values of the loss modulus (E″) and tan δ were established.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, eggshells [20][21][22][23] and clam seashell powder [24] were added as filler materials in PP matrices. Similarly, eggshells have been incorporated into LDPE [25,26], HDPE [27], and poly(vinyl chloride) [28].…”
Section: Introductionmentioning
confidence: 99%